Self‐Powered Gas Sensors: 2D Transition Metal Dichalcogenide Heterostructures for p‐ and n‐Type Photovoltaic Self‐Powered Gas Sensor (Adv. Funct. Mater. 43/2020). (23rd October 2020) - Kim, Youngjun; Lee, Sangyoon; Song, Jeong‐Gyu; Ko, Kyung Yong; Woo, Whang Je; Lee, Suk Woo; Park, Minwoo; Lee, Hoonkyung; Lee, Zonghoon; Choi, Hyunyong; Kim, Woo‐Hee; Park, Jusang; et al.
Abstract : In article number 2003360, Woo‐Hee Kim, Jusang Park, Hyungjun Kim, and co‐workers demonstrate a photovoltaic self‐powered gas sensor using a two‐dimensional (2D) transition metal dichalcogenide (TMD) heterostructure for the first time. The p‐ (WSe2 /WS2 ) and n‐type (MoS2 /WSe2 ) gas sensors exhibit highly sensitive, selective gas sensing properties to NO2 and NH3 gas without external bias due to their photovoltaic features. Further, this study contributes toward revealing the gas sensing mechanism in the 2D TMD heterostructure.